Differential neutralizing antibody responses elicited by CoronaVac and BNT162b2 against SARS-CoV-2 Lambda in Chile - Acevedo, Monica L.; Gaete-Argel, Aracelly; Alonso-Palomares, Luis; de Oca, Marco Montes; Bustamante, Andres; Gaggero, Aldo; Paredes, Fabio; Cortes, Claudia P.; Pantano, Sergio; Martinez-Valdebenito, Constanza; Angulo, Jenniffer; Le Corre, Nicole; et al. (My University, 2022)
The SARS-CoV-2 Lambda variant has been prevalent in Latin America. An analysis of the neutralization capacity of antibodies elicited by CoronaVac and BNT162b2 against SARS-CoV-2 Lambda in plasma from healthcare workers and patients in Chile reveals that BNT162b2 elicits higher neutralizing antibody titres than CoronaVac. SARS-CoV-2 variant Lambda was dominant in several South American countries, including Chile. To ascertain the efficacy of local vaccination efforts, we used pseudotyped viruses to characterize the neutralization capacity of antibodies elicited by CoronaVac (n = 53) and BNT162b2 (n = 56) in healthcare workers from Clinica Santa Maria and the Faculty of Medicine at Universidad de Chile, as well as in convalescent plasma from individuals infected during the first wave visiting the Hospital Clinico at Pontificia Universidad Catolica (n = 30). We observed that BNT162b2 elicits higher neutralizing antibody titres than CoronaVac, with differences ranging from 7.4-fold for the ancestral spike (Wuhan-Hu-1) to 8.2-fold for the Lambda spike and 13-fold for the Delta spike. Compared with the ancestral virus, neutralization against D614G, Alpha, Gamma, Lambda and Delta variants was reduced by between 0.93- and 4.22-fold for CoronaVac, 1.04- and 2.38-fold for BNT162b2, and 1.26- and 2.67-fold for convalescent plasma. Comparative analyses among the spike structures of the different variants suggest that mutations in the spike protein from the Lambda variant, including the 246-252 deletion in an antigenic supersite at the N-terminal domain loop and L452Q/F490S within the receptor-binding domain, may account for immune escape. Interestingly, analyses using pseudotyped and whole viruses showed increased entry rates into HEK293T-ACE2 cells, but reduced replication rates in Vero-E6 cells for the Lambda variant when compared with the Alpha, Gamma and Delta variants. Our data show that inactivated virus and messenger RNA vaccines elicit different levels of neutralizing antibodies with different potency to neutralize SARS-CoV-2 variants, including the variant of interest Lambda.
Keywords: spike protein; Vero cell; Immune escape